WING MACULATION AND GENITALIC VARIATIONS IN THE TYPE - SPECIES ARICIA AGESTIS (DENIS AND SCHIFFERMULLER) (LEPIDOPTERA : LYCAENIDAE) - ROSE, H. S.; SIDHU, A. K (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1996)
The hitherto unrecorded variations in wing maculation of the species, Aricia agestis (Denis and Schiffermuller), which is very common in the North-West Himalaya have been recorded in considerable details. In the male genitalia, the ampulla is surprisingly variable and inconsistent in this biological species. However, all constituent parts of the external female genitalia, studied for the first time, are consistent.